2017
DOI: 10.1103/physrevmaterials.1.044801
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation spectroscopy as a probe of granular superconducting diamond films

Abstract: We present resistance versus temperature data for a series of boron-doped nanocrystalline diamond films whose grain size is varied by changing the film thickness. Upon extracting the fluctuation conductivity near to the critical temperature we observe three distinct scaling regions -3D intragrain, quasi-0D, and 3D intergrain -in confirmation of the prediction of Lerner, Varlamov and Vinokur. The location of the dimensional crossovers between these scaling regions allows us to determine the tunnelling energy an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…31 SB is very thankful to Prof. M. Nesládek (Hasselt University) for providing the samples and conducting stimulating discussions. NRF (SA) and CSIR-NLC are acknowledged for the financial support.…”
mentioning
confidence: 99%
“…31 SB is very thankful to Prof. M. Nesládek (Hasselt University) for providing the samples and conducting stimulating discussions. NRF (SA) and CSIR-NLC are acknowledged for the financial support.…”
mentioning
confidence: 99%
“…We are able to make a very precise determination of T c in these films by fitting to the resistance data using our understanding of the fluctuation conductivity. In a previous work 18 , we have shown that the fluctuation contribution to the conductivity - that is the conductivity due to finite-lifetime Cooper pairs above T c - exhibits a dimensional cross-over into a quasi-zero-dimensional regime. In the approach to the transition, this diverges as σ fl ~ ( T − T c ) −3 , in confirmation of a prediction by Lerner et al .…”
Section: Resultsmentioning
confidence: 86%
“…This glassy dynamics can be attributed to frustration in a system of weakly coupled superconducting clusters, each of which acts as an individual spin 2 . The BNCD films studied here have a granular morphology 15 18 similar to sintered powders, and are close to a metal-insulator transition 19 21 , so that the observation of glassy superconductivity is perhaps not surprising. Nonetheless, this is a novel observation in BNCD films, made possible by detailed analysis of dimensional crossover in fluctuation conductivity 18 – fluctuation spectroscopy –which allows us to probe material properties that are governed by the morphological granularity of our films.…”
Section: Introductionmentioning
confidence: 74%
“…As a result, it becomes more difficult to establish a percolative path for the Cooper pairs, making the condensation and thus the dissipationless flow of Cooper pairs impossible. In this case, a quasi-zero-dimensional state of Cooper pairs, which has been revealed for granular superconducting diamond films by so-called fluctuation spectroscopy [31], can set in and lead to the appearance of an overall insulating phase with localized Cooper pairs. Note that our picture, as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 98%